Human behavior in hazardous situations best practice safety management in the chemical and process industries - Daalmans, Juni (Elsevier Science, 2012)
Human Behavior in Hazardous Situations introduces a new generation within safety management, fully developed with neuropsychological insights, developed in collaboration with, and put to test by, the chemical and process industries. Until now, there has been little theoretical framework on how, and especially why, people behave the way they do in hazardous situations. Human Behavior in Hazardous Situations presents new theories, based on a human behavioral approach, to offer a fresh perspective on safety management. By way of case studies, practical tips and exercises, Dr Jan Daalma